Implementing curriculum at Sekolah Rimba Indonesia - Imaanuddin Muhtar; Haliza Hanif; Winny Azwita Putri; Lisa Amelia (Curricula)
This article discusses implementing policies at Sekolah Rimba Indonesia, founded by Hanan Attaki. Sekolah Rimba adopts a nature-based educational approach and Islamic values, focusing on character development, life skills, and a deep understanding of religion. This article was written with the aim of providing a better understanding of the curriculum provided at Sekolah Rimba so that other schools can later implement this interesting and creative curriculum. The curriculum discussion at Sekolah Rimba was carried out because Sekolah Rimba has a combined curriculum between nature-based and religious education aligned with the current curriculum. Through observation and analysis, this article explores how the Sekolah Rimba curriculum is designed to create a holistic and contextual learning environment. The findings show that the educational methods used at Sekolah Rimba improve students' academic understanding and shape their morals and ethics, resulting in individuals with noble character who make positive contributions to society. This article also provides challenges and successes in implementing these criteria and recommendations for further improvement.